The Combination of AHP (Analytic Hierarchy Process) and SAW (Simple Additive Weighting) Methods in the Selection of Business Locations - Embun Fajar Wati (IJISTECH (International Journal of Information System and Technology), 2021)
Choosing a strategic business location is the dream of entrepreneurs. Site selection can also consider several criteria, namely the bustling market, rental prices, and building area. These criteria become important guidelines in choosing the number of business locations offered. It takes one or several methods used in the decision support system to assist in determining the location of the business. The method used is a combination of AHP (Analytic Hierarchy Process) and SAW (Simple Additive Weighting) which can rank business locations based on predetermined criteria weights. The first step in these methods is the weighting of the criteria based on their level of importance, then proceed with selecting the best alternative by ranking obtained from the results of calculations with both methods. The AHP (Analytic Hierarchy Process) method is used to calculate the weight of each criterion which will be calculated using the normalization matrix of the SAW (Simple Additive Weighting) method. The result of combining these two methods is the best location with the first ranking, namely Poris with a preference value of 0.96. The next ranking is Gondrong, Sipon, Royal, Dadap, Teluk Naga, and the last ranking is Rawa.